Recent advances on electrochemical methods in fabricating two‐dimensional organic‐ligand‐containing frameworks. (4th August 2021) - Wang, Xiang; She, Pengfei; Zhang, Qichun
Abstract: Organic‐ligand‐containing frameworks have drawn considerable attention due to their multifunctional properties as well as tunable structures for broad applications. Among numerous synthesis methods developed in the past two decades, electrochemical processing has been demonstrated as one of the most efficient, safe, and facile ways to realize the large‐scale and highly controllable production of organic‐ligand‐containing frameworks. In this review, the progress of electrochemically induced crystallization and thin film fabrication of organic‐ligand‐containing frameworks is summarized in a well‐rounded way. Besides, the mechanism and processing parameters are also discussed. Moreover, the main challenges are also expounded for providing some guidance on the future development of organic‐ligand‐containing frameworks, especially for covalent‐organic frameworks and hydrogen‐bonded organic frameworks. Abstract : The recent progress in fabricating two‐dimensional organic‐ligand‐containing frameworks through electrochemical process has been reviewed and some guidelines for further research have been provided.